2009
DOI: 10.1353/sof.0.0257
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Specialization, Knowledge Brokerage and the Uneven Growth of Technology Domains

Abstract: Why do certain domains of knowledge grow fast while others grow slowly or stagnate? Two distinct theoretical arguments hold that knowledge growth is enhanced by knowledge specialization and knowledge brokerage. Based on the notion of recombinant knowledge growth, we show that specialization and brokerage are opposing modes of knowledge generation, the difference between them lying in the extent to which homogeneous vs. heterogeneous input ideas get creatively recombined. Accordingly, we investigate how both mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 111 publications
2
89
0
2
Order By: Relevance
“…Innovation researchers have repeatedly used patent data to explore benefits that result from seeking out and combining diverse knowledge (Fleming 2001, Rosenkopf & Nerkar 2001, Nerkar 2003, Fleming, Mingo & Chen 2007, Carnabuci & Bruggeman 2009. Patent data are among our best empirical sources for information about innovation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Innovation researchers have repeatedly used patent data to explore benefits that result from seeking out and combining diverse knowledge (Fleming 2001, Rosenkopf & Nerkar 2001, Nerkar 2003, Fleming, Mingo & Chen 2007, Carnabuci & Bruggeman 2009. Patent data are among our best empirical sources for information about innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation scholarship has found that inventions have more impact when they combine knowledge across technological boundaries than when they draw from a single technology domain (Rosenkopf & Nerkar 2001, Nerkar 2003, Miller, Fern & Cardinal 2007, Carnabuci & Bruggeman 2009, Carnabuci & Operti 2013. The reason is that technological knowledge develops in a cumulative, path-dependent fashion (Dosi 1982, Nerkar 2003, resulting in well-circumscribed knowledge domains (Carnabuci & Bruggeman 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether one relies on biologists, 2 mathematicians, 3 musicians (Gould 1994), or economists (Schumpeter [1942] 2012; Weitzman 1998), there is strong support for the notion that a novel, innovative idea is the result of recombination (Lopes 1992;Hargadon and Bechky 2006;Stark 2009;Carnabuci and Bruggeman 2009). In order to be creative, the team needs the requisite diversity of stylistic elements available for reworking.…”
Section: Cognitive Diversitymentioning
confidence: 99%